Clinicopathological and prognostic value of SNHG6 in cancers: a systematic review and a meta-analysis - Shuo Zhang; Dandan Qiu; Xiaohong Xie; Yong Shen (BMC Cancer, 2020)
Abstract Background Dysregulation of the long non-coding RNA small nucleolar RNA host gene 16 (lncRNA SNHG6) has been found in multiple cancers. However, a definite conclusion on the clinical value of lncRNA SNHG6 expression in human cancers has not been determined. The purpose of the present meta-analysis was to comprehensively elucidate the association between SNHG6 expression and clinical outcomes in cancers. Methods A systematic search was performed through the PubMed, Web of Science, Chinese National Knowledge Infrastructure (CNKI), and Wangfang databases for relevant studies. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were collected to estimate the prognostic value, and the odds ratios (ORs) with 95% CIs were used to evaluate the relationship between lncRNA SNHG6 expression and clinicopathological features, including tumor invasion depth, lymph node metastasis (LNM), distance metastasis (DM), and TNM stage. Results In total, 914 patients from 13 studies were included in this meta-analysis. The pooled results suggested that evaluated SNHG6 expression could predict an unfavorable overall survival (OS) (HR = 2.04, 95% CI:1.56–2.52) with no heterogeneity (I2 = 0.0%, p = 0.996). Subgroup analysis indicated a significant association between high SNHG6 expression and shorter OS in those studies with digestive system cancers (HR = 2.05, 95% CI: 1.47–2.62), or with sample size < 70 (HR = 2.70, 95% CI: 1.29–4.11), or with multivariate analysis (HR = 2.04, 95% CI: 1.44–2.64). Moreover, elevated SNHG6 expression was positively associated with tumor invasion depth (OR = 1.76, 95% CI: 1.18–2.63), LNM (OR = 1.60, 95% CI: 1.18–2.17), DM (OR = 1.90, 95% CI: 1.37–2.64) and advanced TNM stage (OR = 1.88, 95% CI: 1.36–2.60) in patients with cancers. Conclusions High lncRNA SNHG6 expression was correlated with tumor invasion depth, LNM, DM, and advanced TNM stage, suggesting that SNHG6 may serve as a promising prognostic biomarker of human cancers.